Smart Buyer Generation: Cara Mengendalikan Diri dari Impulsive Buying di Era E-Commerce - Budi Prasetiyo; Faqih Ahmad Muzakky (Indo Publishing, 2026)
The development of digital technology and the growth of e-commerce in Indonesia have driven changes in consumer behavior patterns, particularly among adolescents as the digital native generation. The ease of access to online shopping platforms, time-limited promotions such as flash sales, digital payment systems, and paylater features have the potential to increase the tendency toward impulsive buying among school-aged youth. This condition raises concern because weak self-control and low financial literacy can lead to unplanned and risky consumptive behavior in the future. This community service program, titled